Pengaruh ROA, Cash Ratio dan TATO Terhadap Harga Saham Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Nela Rifka Siringoringo; Mila Yulia Herosian; Luhut Piter Simanullang; Christine M.Gabriela Ginting (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
This research intends to see whether ROA (Return on Assets) to some extent affects inventory costs in the area of ??shopper products listed on the Indonesia Stock Exchange for 2016-2020. Does the cash ratio affect the value of inventories in the consumer goods sector listed on the Indonesia Stock Exchange in 2016-2020? Does TATO (Total Asset Turnover Rate) affect inventory costs in the Indonesia Stock Exchange Listed Customer Product Area to some extent in 2016-2020? The performance of ROA, Cash Ratio and TATO simultaneously affect the price of goods in customer portfolios listed on the Indonesia Stock Exchange for the 2016-2020 period. The test method uses quantity. The number of tests in this review is 11 organizations for the 2016-2020 period. Various direct recurrence tests were used in this study. The results of the review show that ROA (Return on Assets) more or less affects inventory costs in the area of ????the goods exchange listed on the Indonesia Stock Exchange in 2016-2020. The cash ratio to a certain extent fundamentally affects inventory costs in the area of ??buyers of products listed on the Indonesia Stock Exchange for the 2016-2020 period. TATO (Full Sourcing Turnover Rate) affects buyers' inventory costs in the Listed Products Area of ??the Indonesia Stock Exchange for 2016-2020 to some extent. ROA, Cash Rartio and TATO fundamentally affect stock prices in the area of ??buyers of products traded on the Indonesia Stock Exchange in 2016-2020. Keywords: ROA, Cash Ratio, TATO and Stock Price